Vertebrate wildlife diversity of Sreepur upazila, Magura, Bangladesh - Mandal, AK; Jaman, MF; Alam, MM; Rabbe, MF; Shome, AR (Journal of Biodiversity Conservation and Bioresource Management, 2022)
The species diversity and abundance of wildlife are the important indicators of a healthy ecosystem. A survey-based scientific study on species diversity, abundance and status of vertebrate wildlife was conducted from May 2015 to April 2016 at Sreepur upazila, Magura, Bangladesh. A total of 123 species of vertebrate wildlife was recorded during the 12 months of study period. Among them, eight species (6.5%) were amphibians, 13 (10.57%) reptiles, 84 (68.29%) birds and 18 species (14.64%) were mammals. Out of 84 species of birds, 45 (53.57%) were passerines and 39 (46.43%) non-passerines. Most of the observed birds (72 species, 85.72%) were resident and the rest 12 species (14.28%) were migratory. The highest number of wildlife species was observed in winter (108 species, 87.80%), particularly in December (62 species, 50.40%). The lowest number of species was recorded in June (33 species, 26.83%). Out of 123 species of vertebrate wildlife, three (2.44%) were very common, nine (7.32%) common, 26 (21.14%) fairly common and 85 (69.1%) were common. Of the total species, 117 (95.12%) species were least concern, five (4.06%) near threatened and one (0.81%) was endangered according to IUCN Bangladesh 2015. Implementation of conservation and management plan is required to save the wildlife in the study area. J. Biodivers. Conserv. Bioresour. Manag. 2021, 7(1): 51-62